Efficient and recyclable aminated black phosphorus / carbon dot / covalent organic framework ternary composite catalyst as well as preparation method and application thereof
By aminating the heterojunction structure of the ternary composite catalyst of black phosphorus/carbon dots/covalent organic framework, the problems of photocatalyst stability and recycling are solved, and an efficient and environmentally friendly benzylamine oxidation and dehydrogenation coupling reaction is achieved. And reduces the risk of metal pollution.
Patent Information
- Application Number
- CN202411185709.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-27
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-08-27
AI Technical Summary
In the benzylamine oxidation and dehydrogenation coupling reaction, existing photocatalysts have problems such as insufficient catalyst stability, metal oozing and difficulty in recycling, and the traditional catalyst preparation process is complicated and not environmentally friendly.
Using aminated black phosphorus/carbon dots/covalent organic skeleton ternary composite catalyst, carbon dots are loaded through mechanical ultrasonic composite and covalent organic skeletons to form a heterojunction structure, enhancing the stability and photocatalytic efficiency of the catalyst, and through metal-free Base materials reduce pollution.
An efficient and environmentally friendly photocatalytic benzylamine oxidation and dehydrogenation coupling reaction is achieved, with a catalytic efficiency of 96.7%, and the catalyst can be recycled to avoid metal contamination.
Smart Images

Figure CN119140157A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalysts, and specifically relates to a highly efficient and recyclable amination black phosphorus / carbon dot / covalent organic skeleton ternary composite catalyst and a preparation method and application thereof. Background Art
[0002] In the field of industrial production, environmental friendliness and economic sustainability have always been the focus of attention. For example, photocatalytic hydrogen production (H 2 ) and photocatalytic conversion of organic matter, etc., to generate value-added compounds in a sustainable and green way, avoiding the consumption of non-renewable fossil fuels or high-energy consumption reaction conditions. As one of the most important intermediates in the production of synthetic pesticides, drugs and bioactive molecules, imines have inspired many researchers to continue to pay attention to and explore their synthesis methods. However, traditional synthesis reactions of imines usually require acidic (or alkaline) and high temperature reaction conditions to drive and catalyze. The yield and product selectivity of these reactions are not ideal, and there are many by-products, resulting in low yield of imines and cumbersome and complicated purification processes. 2 ) atmosphere, the oxidative dehydrogenation coupling reaction of photocatalytic amines is used to prepare imines. This method only requires illumination and pure oxygen environment, is milder than traditional synthesis methods, has lower cost and can greatly reduce the occurrence of side reactions, and reduces the difficulty of purification while improving the yield of imines. The catalyst currently used for the photocatalytic oxidative dehydrogenation coupling reaction of benzylamine is mainly a metal-based photocatalyst (such as metal nanoparticles, metal oxides, metal sulfides, etc.). The preparation process of this type of catalyst often requires high temperature or strong acid and strong base environment, the preparation process is cumbersome and there is a greater risk, and in the subsequent long-term photocatalytic process, there is inevitably a phenomenon of metal seepage in the catalyst, which requires the use of subsequent products to add additional steps of metal separation and purification. This not only further increases the cost, but also has the problem that the catalyst is difficult to reuse and difficult to handle after use, and is prone to metal pollution. Therefore, the design and development of non-metal-based photocatalysts with relatively high photocatalytic efficiency has important application prospects.
[0003] Black phosphorus, as a new type of semiconductor material, has high theoretical specific capacity, fast carrier separation and migration rate, adjustable band gap and low biological toxicity. It has good application prospects in energy storage batteries, catalysis, pharmaceutical carriers and other fields. Monolayer black phosphorus has two different structural directions, the armchair direction and the zigzag direction. This special structure makes the monolayer black phosphorus have significantly different physical properties in each direction. The layers of black phosphorus are fixed together by van der Waals forces, which enables it to be peeled into sheet structures of different thicknesses, and its band gap can be adjusted from 0.3eV to 2.0eV by controlling the thickness of the black phosphorus sheet, so that it has an absorption range from visible light to infrared light. Therefore, it has great potential in photocatalytic hydrogen production, photocatalytic nitrogen fixation, photocatalytic degradation of organic matter and photocatalytic CO2 Reduction and other fields have extensive research and application potential. However, single black phosphorus materials are easily oxidized and have poor stability during the photocatalytic process, and photogenerated electrons and holes are very easy to recombine, which seriously limits the practical application of black phosphorus photocatalysts. Although researchers have proposed many methods to enhance photocatalytic activity and improve stability, including surface modification, covalent functionalization, etc., it is still challenging to achieve relatively efficient photocatalytic technology. As a carbon-based nanomaterial, carbon dots have the advantages of low toxicity, simple and diverse preparation methods, and strong light absorption ability. They are excellent charge carriers and have important application prospects in the field of photocatalysis. The size of carbon dots is usually less than 10nm and is easily soluble in water or organic solvents. Therefore, it is difficult to separate single carbon dot materials during the photocatalytic process, which is not conducive to the purification of products and the recycling of carbon dots. Covalent organic frameworks are porous organic framework materials formed by the polymerization of organic building units. After design, they have the characteristics of large specific surface area, wide absorption spectrum range and low biological toxicity. They also have important application prospects in the field of photocatalysis. A single covalent organic framework has the problem of insufficient conductivity, which limits the improvement of its photocatalytic efficiency.
[0004] In view of the above problems, it is very necessary to study and prepare a non-metal-based photocatalytic material with low toxicity, excellent photocatalytic performance, simple recycling process, and both practical performance and green environmental protection.
[0005] Based on the above reasons, this application is filed. Summary of the invention
[0006] Based on the above reasons, in view of the problems or defects existing in the prior art, the purpose of the present invention is to provide a highly efficient and recyclable aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst and its preparation method and application, so as to solve or at least partially solve the above technical defects existing in the prior art: the new aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared by the present invention can be used for the photocatalytic oxidative dehydrogenation coupling reaction of benzylamine by aminated black phosphorus nanosheets and constructing a heterojunction structure between different materials to improve the stability and photocatalytic efficiency of the composite material.
[0007] In order to achieve one of the above purposes of the present invention, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing an efficient and recyclable amination black phosphorus / carbon dot / covalent organic framework ternary composite catalyst, the method specifically comprising the following steps:
[0009] The aminated black phosphorus nanosheets, carbon dots and covalent organic framework are mixed according to a ratio, and then an appropriate amount of anhydrous ethanol is added. The resulting mixture is subjected to mechanical ultrasonic compounding for 1-2 hours under an inert gas atmosphere and low temperature conditions, and then centrifuged, washed and vacuum dried to obtain the aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst.
[0010] Furthermore, in the above technical solution, the mass ratio of the amino black phosphorus nanosheets, carbon dots, and covalent organic framework is 5:2:2-14:2:2.
[0011] Preferably, in the above technical solution, the mass ratio of the amino black phosphorus nanosheets, carbon dots and covalent organic framework is 9:2:2.
[0012] Furthermore, in the above technical solution, the amount of anhydrous ethanol is not specifically limited, as long as the solid mixture composed of the amino black phosphorus nanosheets, carbon dots and covalent organic framework can be completely and fully mixed. For example, in a preferred embodiment of the present invention, the amount ratio of the solid mixture to anhydrous ethanol is (10-15) parts by mass: 5 parts by volume; wherein: the mass parts and volume parts are based on mg: mL.
[0013] Furthermore, in the above technical solution, the inert gas includes any one of nitrogen or argon, etc. In a preferred embodiment of the present invention, the inert gas is nitrogen.
[0014] Furthermore, in the above technical solution, in a preferred embodiment of the present invention, the low temperature is preferably carried out under ice water bath conditions.
[0015] Furthermore, in the above technical solution, the preparation method of the amino-treated black phosphorus nanosheets is as follows:
[0016] The black phosphorus nanosheets are uniformly dispersed in an N,N-dimethylformamide solution to obtain a black phosphorus nanosheet dispersion; then thionyl chloride and diethylenetriamine are sequentially added to the black phosphorus nanosheet dispersion, and the obtained mixed reaction liquid is heated to 75-85° C. and stirred continuously for 10-15 hours; after the reaction, the obtained product is cooled to room temperature, centrifuged, washed, and vacuum dried to obtain the amino-treated black phosphorus nanosheets.
[0017] Preferably, in the above technical solution, the concentration of the N,N-dimethylformamide solution is 0.2-0.8 mg / mL.
[0018] Preferably, in the above technical solution, the concentration of the black phosphorus nanosheet dispersion is 0.5-0.8 g / mL.
[0019] Preferably, in the above technical solution, the volume ratio of the black phosphorus nanosheet dispersion to thionyl chloride and diethylenetriamine is 50:2:5.
[0020] Preferably, in the above technical solution, in a preferred embodiment of the present invention, the reaction temperature is 80° C. and the reaction time is 12 h.
[0021] Preferably, in the above technical solution, the black phosphorus nanosheets are prepared by subjecting black phosphorus crystals to ball milling for 2-4 hours, ultrasonic peeling for 4-8 hours, centrifugation, and vacuum drying in sequence.
[0022] Furthermore, in the above technical solution, the preparation method of the carbon dots is as follows:
[0023] The citric acid and ethylenediamine are mixed evenly according to the ratio, then added into the polytetrafluoroethylene liner and transferred into the hydrothermal reactor, and the reactor is heated to 180-200° C. for reaction for 5-6 hours; after the reaction is completed, centrifugation, dialyzation with a dialysis membrane with a molecular weight cutoff of 1-2 KDa, and drying to obtain the carbon dots.
[0024] Preferably, in the above technical solution, the usage ratio of citric acid to ethylenediamine is (1-2) g: (335-670) μL.
[0025] Preferably, in the above technical solution, the dialysis time is 12-18 hours.
[0026] Furthermore, in the above technical solution, the preparation method of the covalent organic framework is as follows:
[0027] Phenyltriazole, N,N-dimethylaminoethyl acrylate, toluene, 1,4-dioxane and acetic acid solution are mixed according to a ratio, and the obtained mixed reactant is added to a polytetrafluoroethylene liner and then transferred to a hydrothermal synthesis reactor, and then the reactor is heated to 120-150° C. and reacted for 78-85 hours; after the reaction is completed, the obtained product is centrifuged, washed, vacuum-dried, extracted multiple times in sequence, and finally vacuum-dried to obtain the covalent organic framework.
[0028] Preferably, in the above technical solution, the mass ratio of benzotriazole to N,N-dimethylaminoethyl acrylate is (20-40):(27.4-54.8).
[0029] Preferably, in the above technical solution, the concentration of the acetic acid solution is 3 mol / L-5 mol / L.
[0030] Preferably, in the above technical scheme, the usage ratio of benzotriazole to toluene, 1,4-dioxane and acetic acid solution is (20-40) parts by mass: (0.5-1) parts by volume: (1.5-3) parts by volume: (0.2-0.4) parts by volume; wherein: the mass parts and volume parts are based on mg:mL.
[0031] Preferably, in the above technical solution, the centrifugation and washing steps include centrifuging and washing the obtained reaction product with deionized water, tetrahydrofuran, acetonitrile, and anhydrous ethanol in sequence.
[0032] Preferably, in the above technical solution, the extraction step comprises extraction with tetrahydrofuran, extraction with acetonitrile, extraction with acetone, and extraction with anhydrous ethanol in sequence; and the extraction time of each organic solvent is 3-4 hours.
[0033] The second object of the present invention is to provide an amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared by the above method.
[0034] The third object of the present invention is to provide a ternary composite catalyst of aminated black phosphorus / carbon dots / covalent organic framework prepared by the above method for photocatalytic oxidative dehydrogenation coupling reaction of benzylamine, photocatalytic hydrogen production, photocatalytic CO 2 Application in restoration, etc.
[0035] The present invention provides a photocatalyst for photocatalytic benzylamine oxidative dehydrogenation coupling reaction, comprising an amination black phosphorus / carbon dot / covalent organic skeleton ternary composite catalyst prepared by the method described above. The amination black phosphorus / carbon dot / covalent organic skeleton ternary composite catalyst of the present invention can achieve nearly complete catalysis of the oxidative dehydrogenation coupling reaction of benzylamine within 12 hours.
[0036] The functions of the raw materials used in the present invention are as follows:
[0037] (1) The role of amination of black phosphorus nanosheets is as follows: the present invention adjusts the band gap of black phosphorus nanosheets by controlling the stripping time so that it has a light absorption range that is adapted to the wavelength of the light source, and modifies the surface of black phosphorus nanosheets by amino groups to enhance the active sites at their edges and prevent them from reacting with oxygen or water, thereby enhancing the catalytic effect while enhancing its stability, enhancing the quenching phenomenon of carbon dots, and inhibiting the energy loss caused by the emission of fluorescence from carbon dots, thereby affecting the photocatalytic efficiency.
[0038] (2) The role of carbon dots is: high quantum yield carbon dots form a heterojunction structure with black phosphorus, inhibiting the recombination of photogenerated electrons and holes in black phosphorus, improving the photocatalytic efficiency while also having good photocatalytic efficiency itself, forming a synergistic effect with black phosphorus to further improve the photocatalytic efficiency. The good biocompatibility of carbon dots also facilitates the recycling of the catalyst.
[0039] (3) The function of the covalent organic framework is to form a two-dimensional network structure by connecting organic molecular units through covalent bonds. It is synthesized from at least 8 organic molecular units and integrates structural units with high nitrogen content into the covalent organic framework with advantages such as low skeleton density, high porosity, open pore structure, and large specific surface area. It can load carbon dots and thus more easily construct a better heterojunction structure, thereby promoting photocatalytic reactions. At the same time, it can also form PN bonds with black phosphorus nanosheets to further maintain the stability of black phosphorus nanosheets.
[0040] The application of the high-efficiency and environment-friendly aminated black phosphorus / carbon dots / covalent organic skeleton ternary composite catalyst prepared by the present invention in the field of photocatalysis is as follows: the photocatalytic effect of the aminated black phosphorus nanosheets on the oxidative dehydrogenation coupling reaction of benzylamine in the acetonitrile system reaches 12.3% within 12 hours; the photocatalytic effect of the carbon dots on the oxidative dehydrogenation coupling reaction of benzylamine in the acetonitrile system reaches 41.2% within 12 hours; the photocatalytic effect of the covalent organic skeleton on the oxidative dehydrogenation coupling reaction of benzylamine in the acetonitrile system reaches 13.8% within 12 hours; the catalytic effect of the aminated black phosphorus / carbon dots / covalent organic skeleton ternary composite catalyst is better than that of a single material, indicating that the heterogeneous structure can effectively hinder the recombination of electrons and holes in the black phosphorus nanosheets and improve its photocatalytic performance.
[0041] The present invention uses carbon dots as reinforcements, loads them through a covalent organic framework, and then mixes them with amino black phosphorus nanosheets by mechanical mixing and electrostatic adsorption. After the heterogeneous structure is constructed, a nanocomposite catalyst with excellent photocatalytic effect can be prepared and used as a photocatalyst.
[0042] Compared with the prior art, the present invention has the following beneficial effects:
[0043] (1) The highly efficient and recyclable aminated black phosphorus / carbon dots / covalent organic skeleton ternary composite catalyst prepared by the present invention mainly comprises aminated black phosphorus nanosheets, carbon dots and covalent organic skeletons. The black phosphorus nanosheets are aminated by mechanical ultrasonic compounding to enhance their stability, and a heterojunction structure is formed by the action of electrostatics and chemical bonds, which can reduce the recombination phenomenon of photogenerated electrons and holes in the black phosphorus nanosheets during the photocatalytic process, enhance the quenching phenomenon of carbon dots, and reduce the energy loss caused by fluorescence. The added covalent organic skeleton increases the utilization efficiency of carbon dots and black phosphorus nanosheets by loading carbon dots, so that the final conversion efficiency of 12h reaches 96.7%, which is much higher than that of a single component.
[0044] (2) The composite catalyst of the present invention loads carbon dots through a covalent organic framework, and then forms a heterojunction structure with amino black phosphorus nanosheets to prepare an amino black phosphorus / carbon dots / covalent organic framework ternary composite catalyst. The composite catalyst is economical and environmentally friendly, has excellent chemical stability and efficient photodegradation performance, and is suitable for the field of photocatalysis.
[0045] (3) The present invention uses mechanical mixing and electrostatic adsorption, and the carbon dots are well loaded by the covalent organic skeleton and attached to the surface of the aminated black phosphorus nanosheets, which can not only improve the photocatalytic effect of the catalyst, but also protect the aminated black phosphorus nanosheets from excessive oxidation. The prepared photocatalyst is in powder form, has a large number of active sites, strong adsorption energy, good reaction kinetics and extremely low biological toxicity, and is a composite catalyst with good catalytic efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0047] Figure 1 Schematic diagram of the covalent organic framework structure prepared in Example 1;
[0048] Figure 2 This is the XRD pattern of the black phosphorus nanosheets prepared in Example 1;
[0049] Figure 3 This is a SEM image of the amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 1;
[0050] Figure 4 This is a diagram showing an example of photocatalytic cycle of the amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 1;
[0051] Figure 5 It is a kinetic curve diagram of the amino black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 1. DETAILED DESCRIPTION
[0052] The purpose of the present invention is to solve the problem of insufficient stability of existing black phosphorus-based photocatalysts and easy recombination of photogenerated electrons and holes, and propose a preparation method of a ternary composite catalyst. The advantages of this catalyst are to improve the stability of black phosphorus nanosheets through surface modification and interface action, inhibit the recombination of photogenerated electrons and holes, and improve the catalytic efficiency through the synergistic effect between different materials, and can recover the catalyst for recycling by a simple method. The specific preparation method is as follows:
[0053] A ternary composite catalyst of aminated black phosphorus / carbon dots / covalent organic skeleton is prepared. The composite catalyst uses a covalent organic skeleton to load carbon dots and attaches them to the surface of black phosphorus nanosheets to form a heterojunction structure, thereby obtaining a highly efficient and environmentally friendly photocatalytic product. Since no metal elements are introduced, problems such as metal toxicity and possible metal pollution in subsequent treatment processes can be effectively avoided. At the same time, the elements used to prepare the composite catalyst are all N, C, and P elements that exist in large quantities in nature, and the raw materials are all low-toxic or non-toxic substances, which can reduce chemical pollution and recycling problems as much as possible. The product meets the requirements of energy saving and environmental protection for photocatalysts, has high catalytic efficiency, and can be used in pure oxygen (O 2 ) atmosphere for the oxidative dehydrogenation coupling reaction of photocatalytic amines, and can be recovered and reused after the catalytic reaction is completed.
[0054] The technical solution of the present invention is described in detail below through the accompanying drawings and specific embodiments. The following embodiments are for further explanation of the present invention rather than limiting the scope of the present invention.
[0055] The equipment and raw materials used in the present invention can be purchased from the market or are commonly used in the art. The methods in the following embodiments are all conventional methods in the art unless otherwise specified.
[0056] Example 1
[0057] The preparation method of an amination black phosphorus / carbon dot / covalent organic framework ternary composite catalyst of the present embodiment is as follows:
[0058] Step 1: The preparation method of the amination black phosphorus nanosheets is as follows:
[0059] (1) Preparation of black phosphorus nanosheets
[0060] Black phosphorus crystals (99.998%) and stainless steel balls were loaded into a hardened steel cylinder at a ball-to-powder mass ratio of 500:1 and sealed in an argon-filled glove box. High-energy planetary milling was used in the milling process at a speed of 500r / min. After ball milling for 3h, the powder was placed in anhydrous ethanol and mixed in a volume ratio of 2:3 to form a black phosphorus powder dispersion. The black phosphorus powder dispersion was ultrasonically peeled at a power of 200W at below 5°C for 8h by a cell crusher. After the peeling was completed, the dispersion was centrifuged at a rate of 2000r / min for 20min, and the supernatant was centrifuged again at a rate of 8500r / min for 30min. The precipitate was vacuum dried at 60°C to obtain powdered black phosphorus nanosheets.
[0061] (2) Preparation of amino-modified black phosphorus nanosheets
[0062] The black phosphorus nanosheets prepared in step (1) are dispersed in a 0.5 mg / mL N,N-dimethylformamide solution (prepared by adding N,N-dimethylformamide to anhydrous ethanol) at a concentration of 0.5 g / mL to obtain a black phosphorus nanosheet dispersion; then thionyl chloride (2.0 mL) and diethylenetriamine (5.0 mL) are added to the dispersion, wherein the volume ratio of the black phosphorus nanosheet dispersion, thionyl chloride and diethylenetriamine is 50:2:5; the obtained mixed reaction solution is heated to 80° C. and maintained at the temperature and stirred for 12 h; after the reaction is completed, the heating is stopped and cooled to room temperature, the obtained sample is collected, and centrifuged and washed with N,N-dimethylformamide and anhydrous ethanol at 10000 r / min for 10 min, washed three times until the supernatant is clear, and vacuum dried at 60° C. to obtain amino black phosphorus nanosheets.
[0063] Step 2: The preparation method of the covalent organic framework is as follows:
[0064] 20 mg of benzotriazole (purity of 99.9%), 27.4 mg of acrylic acid-N, N-dimethylaminoethyl ester (purity of 99.9%), 0.5 mL of toluene (purity of 99.9%), 1.5 mL of 1,4-dioxane (purity of 99.9%), and 0.2 mL of 3 mol / L acetic acid solution (prepared by adding acetic acid to deionized water) were mixed in a polytetrafluoroethylene-lined hydrothermal synthesis reactor, and then the reactor was placed in an oven at 120°C for 78 h. After the reaction was completed, deionized water, tetrahydrofuran, and argon were used in turn. Furnace (purity of 99.9%), acetonitrile (purity of 99.9%), and anhydrous ethanol (purity of 99.9%) were centrifuged at 8000r / min for 8min, respectively. After the centrifugation, the samples were vacuum dried. First, tetrahydrofuran was used to extract by Soxhlet extraction for 6h, then acetonitrile was used to extract by Soxhlet extraction for 3h, then acetone (purity of 99.9%) was used to extract by Soxhlet extraction for 3h, and finally anhydrous ethanol was used to extract by Soxhlet extraction for 3h. The final extraction product was vacuum dried at 40°C to obtain a covalent organic framework.
[0065] Step 3: The preparation method of carbon dots is as follows:
[0066] 2 g of citric acid and 670 μL of ethylenediamine were added to a hydrothermal synthesis reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for reaction at 180°C for 6 h. After the reaction, the sample was taken out and centrifuged at 7000 r / min for 10 min. After the centrifugation, the sample was dialyzed for 12 h using a dialysis membrane with a molecular weight cutoff of 1 KDa, and then rotary evaporated at 80°C. Finally, the carbon dots were obtained after vacuum drying at 60°C.
[0067] 10 mg of the aminated black phosphorus nanosheets prepared in the above step 1, the covalent organic framework prepared in the step 2, and the carbon dots prepared in the step 3 were uniformly mixed in a mass ratio of (9:2:2), and placed in 5 mL of anhydrous ethanol. The sample was mechanically ultrasonically compounded at 200 W for 1.5 h under nitrogen protection and ice bath conditions, then centrifuged in a high-speed centrifuge and washed with anhydrous ethanol. The precipitate was then vacuum dried and ground to obtain a sample.
[0068] Figure 1 Schematic diagram of the covalent organic framework structure prepared in Example 1; Figure 2 This is the XRD spectrum of the ultrasonically exfoliated black phosphorus nanosheets in Example 1. The peaks are sharp and narrow, indicating that the black phosphorus nanosheets have good crystallinity and high purity; Figure 3 This is the SEM image of the amino black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 1. The covalent organic framework loaded with carbon dots is loaded in clusters on the black phosphorus nanosheets, indicating the successful construction of the heterojunction structure.
[0069] Example 2
[0070] The preparation method of an amination black phosphorus / carbon dot / covalent organic framework ternary composite catalyst of the present embodiment is as follows:
[0071] Step 1: The preparation method of the amination black phosphorus nanosheets is as follows:
[0072] (1) Preparation of black phosphorus nanosheets
[0073] Black phosphorus crystals (99.998%) and stainless steel balls were loaded into a hardened steel cylinder at a ball-to-powder mass ratio of 500:1 and sealed in an argon-filled glove box. High-energy planetary milling was used in the milling process at a speed of 500r / min. After ball milling for 3h, the powder was placed in anhydrous ethanol and mixed in a volume ratio of 2:3 to form a black phosphorus powder dispersion. The black phosphorus powder dispersion was ultrasonically peeled at a power of 200W at below 5°C for 4h by a cell crusher. After the peeling was completed, the dispersion was centrifuged at a rate of 2000r / min for 20min, and the supernatant was centrifuged again at a rate of 8500r / min for 30min. The precipitate was vacuum dried at 60°C to obtain powdered black phosphorus nanosheets.
[0074] (2) Preparation of amino-modified black phosphorus nanosheets
[0075] The black phosphorus nanosheets prepared in step (1) were dispersed in a 0.5 mg / mL N, N-dimethylformamide solution (preparation method is the same as in Example 1) at a concentration of 0.5 g / mL to obtain a black phosphorus nanosheet dispersion, and then thionyl chloride and diethylenetriamine were added to the dispersion, and the volume ratio of the black phosphorus nanosheet dispersion to thionyl chloride and diethylenetriamine was 50:2:5; the mixed reaction solution obtained was heated to 80°C and maintained at the temperature and stirred for 12 hours. After the reaction was completed, the heating was stopped and cooled to room temperature, and the obtained samples were collected and centrifuged and washed with N, N-dimethylformamide and anhydrous ethanol at 10000 r / min for 10 minutes, washed three times until the supernatant was clear, and dried in vacuo at 60°C to obtain the amination black phosphorus nanosheets.
[0076] Step 2: The preparation method of the covalent organic framework is as follows:
[0077] 20 mg of benzotriazole (purity 99.9%), 27.4 mg of acrylic acid-N, N-dimethylaminoethyl ester (purity 99.9%), 0.5 mL of toluene (purity 99.9%), 1.5 mL of 1,4-dioxane (purity 99.9%), and 0.2 mL of acetic acid solution (concentration 3 mol / L, preparation method is the same as in Example 1) were mixed in a polytetrafluoroethylene-lined hydrothermal synthesis reactor, and then the reactor was placed in an oven at 120° C. for 78 h. After the reaction was completed, deionized water, tetrahydrofuran (purity 99.9%), acetonitrile ( The sample was centrifuged at 8000-9000r / min for 8min, and then dried in vacuo using tetrahydrofuran for 6h, and then using acetonitrile (purity 99.9%) for 3h, and then using acetone (purity 99.9%) for 3h, and finally using anhydrous ethanol (purity 99.9%) for 3h, and finally the extracted product was dried in vacuo at 40°C to obtain a covalent organic framework.
[0078] Step 3: The preparation method of carbon dots is as follows:
[0079] 2 g of citric acid and 670 μL of ethylenediamine were added to a hydrothermal synthesis reactor lined with polytetrafluoroethylene, and the reactor was placed in an oven for reaction at 180°C for 6 h. After the reaction, the sample was taken out and centrifuged at 7000 r / min for 10 min. After the centrifugation, the sample was dialyzed for 12 h using a dialysis membrane with a molecular weight cutoff of 1 KDa, and then rotary evaporated at 80°C. Finally, the carbon dots were obtained after vacuum drying at 60°C.
[0080] 10 mg of the aminated black phosphorus nanosheets prepared in step one, the covalent organic framework prepared in step two, and the carbon dots prepared in step three were uniformly mixed in a mass ratio of 9:2:2, and placed in 5 mL of anhydrous ethanol. The sample was mechanically ultrasonically compounded at 200 W for 1.5 h under nitrogen protection and ice bath conditions, then centrifuged in a high-speed centrifuge and washed with anhydrous ethanol. The precipitate was then vacuum dried and ground to obtain a sample.
[0081] Example 3
[0082] The present embodiment provides a method for preparing an aminated black phosphorus / carbon dots / covalent organic skeleton ternary composite catalyst. While keeping the preparation process of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots in Example 1 unchanged, only the mass ratio of the aminated black phosphorus nanosheets is changed to prepare the catalyst by the same synthesis method. 10 mg of powder of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots prepared in Example 1 are uniformly mixed in a mass ratio of (14:2:2) and placed in 5 mL of anhydrous ethanol. The sample is mechanically ultrasonicated at a power of 200 W for 1.5 h under nitrogen protection, then centrifuged in a high-speed centrifuge and washed with anhydrous ethanol. The precipitate is then vacuum dried and ground to obtain a sample.
[0083] Example 4
[0084] The present embodiment provides a method for preparing an aminated black phosphorus / carbon dots / covalent organic skeleton ternary composite catalyst. While keeping the preparation process of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots in Example 1 unchanged, only the mass ratio of the aminated black phosphorus nanosheets is changed to prepare the catalyst by the same synthesis method. 10 mg of powder of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots prepared in Example 1 are uniformly mixed in a mass ratio of (5:2:2) and placed in 5 mL of anhydrous ethanol. The sample is mechanically ultrasonicated at a power of 200 W for 1.5 h under nitrogen protection, then centrifuged in a high-speed centrifuge and washed with anhydrous ethanol. The precipitate is then vacuum dried and ground to obtain a sample.
[0085] Example 5
[0086] The present embodiment provides a method for preparing an aminated black phosphorus / carbon dots / covalent organic skeleton ternary composite catalyst. While keeping the preparation process of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots in Example 1 unchanged, only the mass ratio of the carbon dots is changed to prepare the catalyst by the same synthesis method. 10 mg of powder of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots prepared in Example 1 are uniformly mixed in a mass ratio of (9:2:1) and placed in 5 mL of anhydrous ethanol. The sample is mechanically ultrasonicated at a power of 200 W for 1.5 h under nitrogen protection, then centrifuged in a high-speed centrifuge and washed with anhydrous ethanol. The precipitate is then vacuum dried and ground to obtain a sample.
[0087] Example 6
[0088] The present embodiment provides a method for preparing an aminated black phosphorus / carbon dots / covalent organic skeleton ternary composite catalyst. While keeping the preparation process of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots in Example 1 unchanged, only the mass ratio of the carbon dots is changed to prepare the catalyst by the same synthesis method. 10 mg of powder of the aminated black phosphorus nanosheets, covalent organic skeletons and carbon dots prepared in Example 1 are uniformly mixed in a mass ratio of (9:2:3) and placed in 5 mL of anhydrous ethanol. The sample is mechanically ultrasonicated at a power of 200 W for 1.5 h under nitrogen protection, then centrifuged in a high-speed centrifuge and washed with anhydrous ethanol. The precipitate is then vacuum dried and ground to obtain a sample.
[0089] Comparative Example 1
[0090] The present comparative example provides a method for preparing an aminated black phosphorus catalyst. While keeping the preparation process of the aminated black phosphorus nanosheets in Example 1 unchanged, only the aminated black phosphorus nanosheets are used to prepare the catalyst by the same synthesis method. 10 mg of powder of the aminated black phosphorus nanosheets prepared in Example 1 is taken and placed in 5 mL of anhydrous ethanol. The sample is mechanically ultrasonicated at a power of 200 W for 1.5 h under nitrogen protection, then centrifuged in a high-speed centrifuge, washed with anhydrous ethanol, and then the precipitate is vacuum dried and ground to obtain a sample.
[0091] Comparative Example 2
[0092] A method for preparing a carbon dot catalyst in this comparative example is to use carbon dots to prepare a catalyst by the same synthesis method while keeping the preparation process of the carbon dots in Example 1 unchanged. 10 mg of the carbon dots prepared in Example 1 are taken as powder and placed in 5 mL of anhydrous ethanol. The sample is mechanically ultrasonicated at a power of 200 W under nitrogen protection for 1.5 h, then centrifuged in a high-speed centrifuge and washed with anhydrous ethanol. The precipitate is then vacuum dried and ground to obtain a sample.
[0093] Comparative Example 3
[0094] A method for preparing a covalent organic skeleton catalyst in this comparative example, while keeping the preparation process of the covalent organic skeleton in Example 1 unchanged, only the covalent organic skeleton is used to prepare the catalyst by the same synthesis method, 10 mg of the covalent organic skeleton prepared in Example 1 is taken as powder, and placed in 5 mL of anhydrous ethanol, the sample is mechanically ultrasonicated at a power of 200 W under nitrogen protection for 1.5 h, then centrifuged in a high-speed centrifuge, washed with anhydrous ethanol, and then the precipitate is vacuum dried and ground to obtain a sample.
[0095] Application Example 1
[0096] The aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 1 was used for the photocatalytic oxidative dehydrogenation coupling reaction of benzylamine, and the specific steps were as follows:
[0097] 10 mg of the catalyst sample prepared in Example 1 was placed in a 10 mL glass test tube, 20 μL of benzylamine and 4 mL of acetonitrile were added thereto, and then a magnetic bar was added, and it was ultrasonically mixed for 20 min at a power of 200 W in a water bath temperature below 50° C. After the mixing was completed, oxygen was blown into the glass test tube for 1 min to keep the reaction system closed, and then stirred and illuminated for 12 h under a light source with a power of 30 W and a wavelength of 365 nm.
[0098] Application Example 2
[0099] The application method used in this application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this application example is the amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 2.
[0100] Application Example 3
[0101] The application method used in this application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this application example is the amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 3.
[0102] Application Example 4
[0103] The application method used in this application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this application example is the amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 4.
[0104] Application Example 5
[0105] The application method used in this application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this application example is the amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 5.
[0106] Application Example 6
[0107] The application method used in this application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this application example is the amination black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 6.
[0108] Comparative application example 1
[0109] The application method used in this comparative application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this comparative application example is the amination black phosphorus catalyst prepared in Comparative Example 1.
[0110] Comparative Application Example 2
[0111] The application method used in this comparative application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this comparative application example is the carbon dot catalyst prepared in Comparative Example 2.
[0112] Comparative Application Example 3
[0113] The application method used in this comparative application example is basically the same as that used in Application Example 1, with the only difference being that the catalyst sample used in this comparative application example is the covalent organic framework catalyst prepared in Comparative Example 3.
[0114] Comparison Example
[0115] Take 20 μL of benzylamine and 4 mL of acetonitrile and place them in a glass test tube. Add a magnetic bar and mix them by ultrasonication at a power of 200 W for 20 min in a water bath temperature below 50°C. After the mixing is completed, blow oxygen into the glass test tube for 1 min to keep the reaction system closed. Stir and illuminate for 12 h under a light source with a power of 30 W and a wavelength of 365 nm.
[0116] Test result analysis:
[0117] The difference between Application Example 1 and Application Example 2 is that the ultrasonic time of the added aminated black phosphorus nanosheets is different. From the data in Table 1, it can be seen that the system of Application Example 1 with the addition of aminated black phosphorus nanosheets for 8 hours can effectively photocatalyze the oxidative dehydrogenation coupling reaction of benzylamine, while the degradation effect of the system of Application Example 2 with the addition of aminated black phosphorus nanosheets for 4 hours is greatly reduced. Therefore, it is concluded that the ultrasonic time of aminated black phosphorus nanosheets has a great influence on the photocatalytic effect.
[0118] The difference between Application Example 1, Application Example 3 and Application Example 4 lies in the content of aminated black phosphorus nanosheets added in the composite catalyst. The purpose of formulating this scheme is to analyze the optimal ratio of aminated black phosphorus nanosheets for the composite catalyst. While changing the content of aminated black phosphorus nanosheets, the mass fractions of the other two materials are changed. In addition to proving that 9 / 13 (specifically referring to the mass proportion of aminated black phosphorus nanosheets in the composite catalyst) is the optimal ratio of aminated black phosphorus nanosheets, it is further proved that the aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst can effectively catalyze the oxidative dehydrogenation coupling reaction of benzylamine under 356nm light conditions.
[0119] The difference between Application Example 1, Application Example 5 and Application Example 6 lies in the content of carbon dots added in the composite catalyst. The purpose of formulating this scheme is to analyze the optimal carbon dot ratio of the composite catalyst. While changing the carbon dot content, the mass fractions of the other two materials are changed. In addition to proving that 2 / 13 (specifically referring to the mass proportion of carbon dots in the composite catalyst) is the optimal carbon dot ratio, it further proves that the amino black phosphorus / carbon dots / covalent organic framework ternary composite catalyst can effectively catalyze the oxidative dehydrogenation coupling reaction of benzylamine under 356nm light conditions.
[0120] Comparative Application Example 1, Comparative Application Example 2 and Comparative Application Example 3 distinguish the components of the catalyst. From the data in Table 1, it can be seen that the catalytic effects of the three material monomers under 365nm light conditions for 12h are not good, less than 50%. It also further illustrates the formation of heterojunction structure and the catalytic effect of the amino black phosphorus / carbon dot / covalent organic framework ternary composite catalyst.
[0121] The difference between the control example and other application examples and comparative application examples is whether a catalyst is added, which eliminates the influence of a series of processes that may cause benzylamine autocatalysis due to time, temperature, ultrasound, stirring, etc., and further increases the credibility and accuracy of the results of other schemes.
[0122] The specific calculation formula of the benzylamine catalytic conversion rate recorded in Table 1 and Table 2 is as follows:
[0123]
[0124] Table 1 Benzylamine catalytic conversion rate in different application examples
[0125] plan Amount of benzylamine added before reaction / μmol The amount of benzylamine remaining after the reaction / μmol Conversion rate / % Application Example 1 4.38 0.14 96.7 Application Example 2 4.38 2.12 51.7 Application Example 3 4.38 2.42 44.8 Application Example 4 4.38 2.03 53.6 Application Example 5 4.38 1.55 64.7 Application Example 6 4.38 1.42 97.6 Comparative application example 1 4.38 3.84 12.3 Comparative Application Example 2 4.38 2.58 41.2 Comparative Application Example 3 4.38 3.78 13.8 Comparison Example 4.38 4.09 6.7
[0126] Table 2 Kinetic test of catalytic conversion rate of benzylamine in application example 1
[0127] Reaction time / h Amount of benzylamine added before reaction / μmol The amount of benzylamine remaining after the reaction / μmol Conversion rate / % 2 4.38 3.07 29.9 4 4.38 2.56 41.6 6 4.38 1.79 59.1 8 4.38 1.19 72.8 10 4.38 0.63 85.6 12 4.38 0.15 96.7
[0128] Photocatalytic cycle stability test:
[0129] The photocatalytic cycle experiment is to wash the ternary composite catalyst sample of Example 1 three times by centrifugation with anhydrous ethanol after the first cycle experiment, and then take 10 mg of the sample after vacuum drying at 60°C to perform the second cycle experiment under the reaction conditions of Example 1. Finally, the third cycle experiment is performed in the same steps. Multiple samples are prepared repeatedly for each cycle experiment to ensure that enough samples can be provided for the next cycle experiment, and 4 samples are selected from the multiple samples, and the post-reaction solution is taken out at the required time and tested by liquid chromatograph to obtain experimental data.
[0130] Figure 4 This is a diagram of the photocatalytic cycle experimental efficiency of the aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared in Example 1. It can be seen that after three cycle experiments with the same steps, the aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst still has a catalytic effect of more than 60%, proving that it has good stability.
[0131] Figure 5 The kinetic curve of the ternary composite catalyst of amino black phosphorus / carbon dots / covalent organic framework prepared in Example 1 is shown; the experiment of Example 1 is repeated 6 times, and the solution is sampled at reaction times of 2h, 4h, 6h, 8h, 10h, and 12h in 6 groups of experiments without repeated sampling. The 6 samples are tested by liquid chromatograph to obtain experimental data and draw a kinetic curve. It can be seen that the catalytic effect curve rises smoothly, and the catalytic effect at 2h reaches 29.9%, the catalytic effect at 4h reaches 41.6%, the catalytic effect at 6h reaches 59.1%, the catalytic effect at 8h reaches 72.8%, the catalytic effect at 10h reaches 85.6%, and the catalytic effect at 12h has reached 96.7%, which is close to complete catalysis. The average catalytic rate in the first 6 hours is close to 9.9%, the average catalytic rate in the first 10 hours is close to 8.6%, and the average catalytic rate in 12 hours is close to 8.1%, which proves that when the concentration of the reactants is reduced to a certain level, the catalytic effect will be reduced. However, the average minimum catalytic effect per hour still reaches more than 8%, and the average maximum catalytic effect can reach more than 10%, which proves its good catalytic effect.
[0132] For those skilled in the art, the present invention is not limited to the details of the above exemplary embodiments, and without departing from the spirit or scope of the principles of the present invention, the changes, modifications, substitutions, etc. made can implement the mode of the present invention in the form of other equivalent substitutions. Therefore, the embodiments of the present invention are exemplary and non-restrictive. The scope of the present invention shall be limited by the attached claims rather than the above description, and all modifications and improvements made to the technical solution of the present invention that fall within the meaning and scope of the equivalent elements of the claims shall fall within the scope of protection determined by the claims of the present invention.
Claims
1. A method for preparing an efficient and recyclable aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst, characterized in that: The method specifically comprises the following steps: The aminated black phosphorus nanosheets, carbon dots and covalent organic framework are mixed according to a ratio, and then an appropriate amount of anhydrous ethanol is added. The resulting mixture is subjected to mechanical ultrasonic compounding for 1-2 hours under an inert gas atmosphere and low temperature conditions, and then centrifuged, washed and vacuum dried to obtain the aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the amino black phosphorus nanosheets, carbon dots and covalent organic framework is 5:2:2-14:2:
2.
3. The preparation method according to claim 1, characterized in that: The preparation method of the amination black phosphorus nanosheet is as follows: The black phosphorus nanosheets are uniformly dispersed in an N,N-dimethylformamide solution to obtain a black phosphorus nanosheet dispersion; then thionyl chloride and diethylenetriamine are sequentially added to the black phosphorus nanosheet dispersion, and the obtained mixed reaction liquid is heated to 75-85° C. and stirred continuously for 10-15 hours; after the reaction, the obtained product is cooled to room temperature, centrifuged, washed, and vacuum dried to obtain the amino-treated black phosphorus nanosheets.
4. The preparation method according to claim 3, characterized in that: The volume ratio of the black phosphorus nanosheet dispersion to thionyl chloride and diethylenetriamine is 50:2:
5.
5. The preparation method according to claim 1, characterized in that: The preparation method of the carbon dots is as follows: The citric acid and ethylenediamine are mixed evenly according to the ratio, then added into the polytetrafluoroethylene liner and transferred into the hydrothermal reactor, and the reactor is heated to 180-200° C. for reaction for 5-6 hours; after the reaction is completed, centrifugation, dialyzation with a dialysis membrane with a molecular weight cutoff of 1-2 KDa, and drying to obtain the carbon dots.
6. The preparation method according to claim 5, characterized in that: The usage ratio of citric acid to ethylenediamine is (1-2) g: (335-670) μL.
7. The preparation method according to claim 1, characterized in that: The preparation method of the covalent organic framework is as follows: Phenyltriazole, N,N-dimethylaminoethyl acrylate, toluene, 1,4-dioxane and acetic acid solution are mixed according to a ratio, and the obtained mixed reactant is added to a polytetrafluoroethylene liner and then transferred to a hydrothermal synthesis reactor, and then the reactor is heated to 120-150° C. and reacted for 78-85 hours; after the reaction is completed, the obtained product is centrifuged, washed, vacuum-dried, extracted multiple times in sequence, and finally vacuum-dried to obtain the covalent organic framework.
8. A ternary composite catalyst of aminated black phosphorus / carbon dots / covalent organic framework prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the aminated black phosphorus / carbon dots / covalent organic framework ternary composite catalyst prepared by the preparation method according to any one of claims 1 to 7 in photocatalytic oxidative dehydrogenation coupling reaction of benzylamine, photocatalytic hydrogen production, and photocatalytic CO2 reduction.
10. A photocatalyst for photocatalytic benzylamine oxidative dehydrogenation coupling reaction, characterized in that: The invention comprises a ternary composite catalyst of aminated black phosphorus / carbon dots / covalent organic framework prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Trititanium dicarbide / titanium dioxide / black phosphorus nanosheet composite photocatalyst, and preparation method and application thereof
CN111185210A
BPQDs / MoO3 / ZnIn2S4 ternary heterostructure composite photocatalytic material as well as preparation method and application thereof
CN115463671A
D-A type covalent organic framework composite molybdenum disulfide lamellar material as well as preparation method and application thereof
CN118491568A
